Handling and storage of human body fluids for analysis of extracellular vesicles. Issue 1 (11th November 2015) - Yuana, Yuana; Böing, Anita N.; Grootemaat, Anita E.; van der Pol, Edwin; Hau, Chi M.; Cizmar, Petr; Buhr, Egbert; Sturk, Auguste; Nieuwland, Rienk
Abstract : Because procedures of handling and storage of body fluids affect numbers and composition of extracellular vesicles (EVs), standardization is important to ensure reliable and comparable measurements of EVs in a clinical environment. We aimed to develop standard protocols for handling and storage of human body fluids for EV analysis. Conditions such as centrifugation, single freeze–thaw cycle, effect of time delay between blood collection and plasma preparation and storage were investigated. Plasma is the most commonly studied body fluid in EV research. We mainly focused on EVs originating from platelets and erythrocytes and investigated the behaviour of these 2 types of EVs independently as well as in plasma samples of healthy subjects. EVs in urine and saliva were also studied for comparison. All samples were analysed simultaneously before and after freeze–thawing by resistive pulse sensing, nanoparticle tracking analysis, conventional flow cytometry (FCM) and transmission (scanning) electron microscopy. Our main finding is that the effect of centrifugation markedly depends on the cellular origin of EVs. Whereas erythrocyte EVs remain present as single EVs after centrifugation, platelet EVs form aggregates, which affect their measured concentration in plasma. Single erythrocyte and platelet EVs are present mainly in the range of 100–200 nm, far below the lower limit of what can be measured by conventional FCM. Furthermore, the effects of single freeze–thaw cycle, time delay between blood collection and plasma preparation up to 1 hour and storage up to 1 year are insignificant ( p >0.05) on the measured concentration and diameter of EVs from erythrocyte and platelet concentrates and EVs in plasma, urine and saliva. In conclusion, in standard protocols for EV studies, centrifugation to isolate EVs from collected body fluids should be avoided. Freezing and storage of collected body fluids, albeit their insignificant effects, should be performed identically for comparative EV studies and to create reliable biorepositories.